IKLIM ORGANISASI, KINERJA DAN EFEKTIVITAS KERJA ORGANISASI - Soleha, Putri Ayu; Heriyanto, Meyzi; Sahuri, Chalid (Jurnal Ilmu Administrasi Negara, 2018)
Organizational Climate, Performance and Organizational Effectiveness. The study intends to find out the extent of the influence of the climate of ogranization and the organization's performance on the effectiveness of deconcentration fund management of government affairs in Riau Province. The method of this research is quantitative method with total population of 53 people. Data collection was done by direct research, interview and questionnaire. Then tested the validity and reliability, classical assumption test of data and multiple regression analysis using SPSS 16. The results showed that climate organization and organizational performance influence simultaneously on the effectiveness of deconcentration fund management government affairs with a contribution of 71.6%. While the rest of 28.4% influenced by other factors not examined in this study.